Prototyping a low-cost open-source autonomous unmanned surface vehicle for real-time water quality monitoring and visualization. (October 2022) - Ryu, Jae Hyeon
Graphical abstract: Abstract: A low-cost open-source autonomous unmanned surface vehicle (USV) named "iDroneboat" is developed for real-time monitoring and visualization of water quality. The iDroneboat equipped with Internet of Things (IoT) sensors transmits real-time water quality data, including dissolved oxygen (DO), electronical conductivity (EC), pH, and water temperature (WT) to the cloud for data sharing through Long-term Evolution (LTE) communication protocols. Since material and supplies needed are readily accessible from online marketplaces or local hardware stores, the iDroneboat is easily replicable for local water quality studies and citizen-science activities. The iDroneboat appears to be a promising tool to advance environmental research activities, especially for impaired waterways ( e.g., lakes, rivers, and reservoirs). The preliminary result shows that the proposed low-cost platform, iDroneboat, effectively displays water quality components in real-time to the cloud web services ( e.g., ThingSpeak), ultimately contributing to citizen science activities and environmental stewardship in water research ecosystems.